Effect of Molecular Architecture on Cell Interactions and Stealth Properties of PEG - Ozer, Imran; Tomak, Aysel; Zareie, Hadi M.; Baran, Yusuf; Bulmus, Volga (Amer Chemical Soc, 2017)
PEGylation, covalent attachment of PEG to therapeutic biomolecules, in which suboptimal pharmacokinetic profiles limiting their therapeutic utility are of concern, is a widely applied technology. However, this technology has been challenged by reduced bioactivity of biomolecules upon PEGylation and immunogenicity of PEG triggering immune response and abrogating clinical efficacy, which collectively necessitate development of stealth polymer alternatives. Here we demonstrate that comb-shape poly[oligo(ethylene glycol) methyl ether methacrylate](POEGMA); a stealth polymer alternative, has a more compact structure than PEG and self-organize into nanoparticles in a molecular weight dependent manner. Most notably, we show that comb shape POEGMA promotes significantly higher cellular uptake and exhibits less steric hindrance imposed on the conjugated biomolecule than PEG. Collectively, comb-shape POEGMA offers a versatile alternative to PEG for stealth polymer-biomolecule conjugation applications.
Baran, Yusuf/0000-0002-1056-4673; Bulmus, Volga/0000-0001-9944-1444